Fluorescence assay of oxytetracycline in seawater after selective capture using magnetic molecularly imprinted nanoparticles. (February 2021) - Zhao, Min; Wang, Jiangtao; Lian, Ziru
Abstract: A comprehensive strategy for manufacturing a novel sorbent based on magnetic molecularly imprinted polymers (MMIPs) is addressed for selective capture of oxytetracycline from seawater. The novel MMIPs were synthesized by nano-Fe3 O4 as sacrificial matrix and adsorption properties of the polymers demonstrate rapid adsorption kinetics, high adsorption capacity, and specificity towards oxytetracycline provided by the core-shell composite structure. After screening the critical parameters by multivariate optimization, a magnetic imprinting solid phase extraction method combined with fluorescence spectrophotometry (MMIP-SPE-FL) was constructed for sensitive determination of oxytetracycline in seawater samples. The results show a good linear response dependence on the spiking concentration of 3–100 μg L −1, and a satisfactory limit of detection of 0.7 μg L −1 after the MMIP-SPE preconcentration. Seven seawater samples from Jiaozhou bay were analyzed to give recoveries in the range of 89.75–107.65% with relative standard deviation values of less than 5.44% (n = 3). Graphical abstract: Unlabelled Image Highlights: Magnetic imprinted nanoparticles for oxytetracycline (OTC-MMIPs) were prepared. The MMIPs showed remarkable adsorption capacity, kinetics and selectivity. A MMIP-SPE procedure was developed for OTC selective extraction from seawater. Seawater samples from Jiaozhou bay were effectively analyzed by MMIP-SPE-FL.